Milestone Dan Makna Ornamen Puri Agung Karangasem Dalam Persfektif Hermeneutika - Laba, I Nyoman; Adnyana, I Wayan; Muka, I Ketut; Suardana, I Wayan; Gede Artayani, Ida Ayu (PANGGUNG, 2025)
The architecture of Puri Agung Karangasem shows important achievements in architectural progress and the trajectory of the meaning of ornaments shows the acculturation of Balinese, Chinese, and European cultures. Researchers have not found research on the milestones and meaning of ornaments in the Puri. The purpose of this research is to explain the important historical achievements and the meaning of architectural ornaments of Puri Agung Karangasem. A qualitative descriptive method is implemented to explain the milestones and meaning of architectural ornaments of Puri Agung Karangasem. Hermeneutic theory is used as an approach to uncover the historicity and interpretation of the meaning of the architectural ornaments of the Puri. Data collection techniques include observation, interviews and documentation, while as a source of data are ornaments on palace architecture, cultural experts, community leaders, and as key informants of Penglingsir Puri and Abdi Dalem Puri. The results of the study show that the architecture of Puri Agung Karangasem has a very important meaning and achievement in the history of Bali, especially in the context of the kingdom. The forms of ornaments found in Puri Agung Karangasem can be distinguished into three, namely ornaments in traditional Balise, Chinese and European styles, resulting in a combination of typical ornamental forms of Puri Agung Karangasem. From a hermeneutic perspective, these ornaments are signs that refer to certain aspects of social, religious, and political life in Bali, especially the kingdom of Karangasem. In addition, the ruler of Puri Agung Karangasem in ancient times had a fairly good cultural relationship with people from China and Europe, as reflected in the visualization of ornaments integrated into the architecture of the Puri.